Own experience with implantation of new stentless valve Freedom SOLO® - Pawlak, Szymon; Niklewski, Tomasz; Śliwka, Joanna; Foremny, Jerzy; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
In June 2009 in Silesian Center for Heart Diseases in Zabrze a new aortic stentless tissue valve Sorin Freedom SOLO ® was first implanted. During the next twelve months this bioprothesis was successfuly implanted in 59 patients. To assess the results and usfulness of the prothesis we used we analysed the echocardiografic variables of the 20 patients with preoperatively diagnosed norrow (< 23 mm) aortic ring diameter. The results were compared with the similar groups of the patients after another aortic prothesis implantation (St. Jude Medical EPIC ® ). Regarding the previously printed articles reporting severe thrombocytopenia (PLT < 150 × 103/µl) occuring after Sorin Freedom SOLO ® implantation we analysed three 40 pts groups after stentless and stented tissue valve implantation and after coronary-aortic bypass grafting. No statistically significant differencess in platelet count was found between those groups. This Sorin Freedom SOLO ® valve presents also very low flow gradient, both mean – 10.3 mm Hg and maximum – 21.6 mm Hg. In the patients group with the stentless tissue valve implanted the most left ventricle mass reduction (29%) was observed. In conclusion, aortic stentless tissue valve Sorin Freedom SOLO® is a good proposition for parients with narrowed aortic ring diameter in whitch bioprothesis implantation is required.